Queue questions: ethics of COVID-19 vaccine prioritization - Giubilini, A; Savulescu, J; Wilkinson, D (Wiley, 2021)
The rapid development of vaccines against COVID-19 represents a huge achievement, and offers hope of ending the global pandemic. At least three COVID-19 vaccines have been approved or are about to be approved for distribution in many countries. However, with very limited initial availability, only a minority of the population will be able to receive vaccines this winter. Urgent decisions will have to be made about who should receive priority for access. Current policy in the UK appears to take the view that those who are most vulnerable to COVID-19 should get the vaccine first. While this is intuitively attractive, we argue that there are other possible values and criteria that need to be considered. These include both intrinsic and instrumental values. The former are numbers of lives saved, years of life saved, quality of the lives saved, quality-adjusted life-years (QALYs), and possibly others including age. Instrumental values include protecting healthcare systems and other broader societal interests, which might require prioritizing key worker status and having dependants. The challenge from an ethical point of view is to strike the right balance among these values. It also depends on effectiveness of different vaccines on different population groups and on modelling around cost-effectiveness of different strategies. It is a mistake to simply assume that prioritizing the most vulnerable is the best strategy. Although that could end up being the best approach, whether it is or not requires careful ethical and empirical analysis.